Neuromuscular electrical stimulation during maximal voluntary contraction: a Delphi survey with expert consensus - Osborne, J. O.; Tallent, J.; Girard, O.; Marshall, P. W.; Kidgell, D.; Buhmann, R. (European Journal of Applied Physiology, 2023)
Purpose The use of electrical stimulation to assess voluntary activation of muscle/s is a popular method employed in numerous exercise science and health research settings. This Delphi study aimed to collate expert opinion and provide recommendations for best practice when using electrical stimulation during maximal voluntary contractions.